The evolution of gender equality and related employment policies: The case of work–family reconciliation. Issue 2 (June 2018) - Busby, Nicole
European Union (EU) law and policy on work–family reconciliation has developed by way of two parallel but often incoherent movements. The jurisprudence of the Court of Justice of the EU has been a driving force in its interpretation of sex discrimination provisions in the context of claims concerning women's labour market experiences, which have subsequently been codified, for example, to provide positive rights in relation to pregnancy and maternity. Alongside this development, policy has been linked to wider economic concerns such as the goal of full employment leading to specific measures intended to equalize employment conditions for those with non-standard working arrangements and to encourage shared parenting between men and women. The lack of a specific focus on work–family reconciliation as a goal for law and policy in its own right has resulted in a patchwork of provisions rather than an overarching framework. The net result is that EU law provides an unsatisfactory response to what has been termed the unsolved conflict between paid work and unpaid care. Recent developments may provide a solution. The Commission has reinvigorated its interest through its 'New Start' initiative – a package of both legislative and non-legislative measures under the auspices of the European Pillar of Social Rights launched in April 2017. Provisions incorporate, inter alia, a proposed directive that would amend the parental leave regime and introduce paid paternity and carers' leave. This article provides a critique of law and policy to date and assesses the potential for a coordinated EU strategy for work–family reconciliation, focusing specifically on gender equality. It is argued that, even with the enhanced interest of the Commission, it may be difficult to achieve a coordinated approach to what has always been a contentious policy area within a rapidly changing EU although the United Kingdom's departure from the EU may provide an opportunity in this respect.